Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1073/pnas.93.23.12937
|View full text |Cite
|
Sign up to set email alerts
|

Torsional rigidity of single actin filaments and actin–actin bond breaking force under torsion measured directly by in vitro  micromanipulation

Abstract: Knowledge of the elastic properties of actin filaments is crucial for considering its role in muscle contraction, cellular motile events, and formation of cell shape. The stiffness of actin filaments in the directions of stretching and bending has been determined. In this study, we have directly determined the torsional rigidity and breaking force of single actin filaments by measuring the rotational Brownian motion and tensile strength using optical tweezers and microneedles, respectively. Rotational angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
204
6
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(239 citation statements)
references
References 31 publications
26
204
6
2
Order By: Relevance
“…With direct imaging, on the other hand, Suzuki et al (1996) have analyzed the motion of bead aggregates bound to the tail of an actin filament and estimated the torsional rigidity of F-actin to be of a magnitude similar to our values. Tsuda et al (1996) have also suggested a similar value.…”
Section: Comparison With Previous Studiessupporting
confidence: 48%
“…With direct imaging, on the other hand, Suzuki et al (1996) have analyzed the motion of bead aggregates bound to the tail of an actin filament and estimated the torsional rigidity of F-actin to be of a magnitude similar to our values. Tsuda et al (1996) have also suggested a similar value.…”
Section: Comparison With Previous Studiessupporting
confidence: 48%
“…These would be either ruptures of thin actin filaments from Z-disks and/or ruptures of Z-disk components as comparable ruptures were not observed for calpaintreated myofibrils. Alternatively, they could be due to the splitting of actin filaments, 250-550 pN (Tsuda et al, 1996), and/or intramolecular ruptures of connectin filaments, about 200 pN (Li et al, 2002). Notably, in the AFM experiments, the ruptures that took place in trypsin-treated and calpain-treated myofibrils were significantly smaller in magnitude than those that took place in intact myofibrils in rigor and relaxed states (Fig.…”
Section: Characteristic Ruptures Of Peripheral Components Of Myofibrilsmentioning
confidence: 94%
“…The actin filaments were stretched and eventually severed into two filaments, in which each end of the filament remained attached to the beads in all the cases examined. This indicates that the binding strength between actin filaments and α-actinin-coated beads is greater than the tensile force to split single actin filaments, 250-550 pN (Tsuda et al, 1996).…”
Section: Attachment Of α-Actinin-coated Beads To the Surface Of Myofimentioning
confidence: 99%
See 1 more Smart Citation
“…The zeroth order variables for the effective rod frame U (0) ir are obtained by substitution of the U (0) i into (43) - (45). Note that θ has no expansion and hence no labelling, it is the zeroth order form of the angles α i which we do expand.…”
Section: The Zeroth Order System:-a Summarymentioning
confidence: 99%